Uncommon Presentation of Testicular Anomaly: An Insight into Tuberculous Orchitis Diagnostic Challenges in Rural Settings - Syarif, Syarif; Kembaren, Jefry Sondang; Yandhi, Jeffry (Brawijaya Journal of Urology, 2026)
Introduction. Testicular tuberculosis is very rare, accounting for only 3% of genital tuberculosis cases. Diagnosing testicular tuberculosis is challenging and often only confirmed through post-surgical histopathological findings after an orchiectomy. Case. A 59-year-old male patient came in complaining of a painless, gradually developing expansion in his left testicle. The patient did not have a history of tuberculosis or any related symptoms, including fever, appetite loss, respiratory issues, or significant weight loss. Physical examination and ultrasound suggested a testicular tumor. Due to the absence of definite preoperative diagnostic methods in our settings, we diagnosed the patient with a testicular tumor. Consequently, a left orchiectomy was performed, and the pathologic examination revealed tuberculous orchitis. Conclusion. Given the limited diagnostic tools available and the elusiveness of similar cases encountered, surgery followed by histopathological findings for both treatment and diagnosis might be unavoidable in many cases.